2017
DOI: 10.31235/osf.io/r2hfb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The path from social origins to top jobs: social reproduction via education

Abstract: This paper provides a comprehensive account of the way in which cognitive and educational attainment mediate the link between social origins and elite social class destinations in mid-life. Using the 1970 British Cohort Study (BCS70), we assess the roles of a range of pathways through which educational advantage may lead to occupational attainment: cognitive development; private and selective secondary schools; school level qualifications; and higher education, including institution and field of study. Whereas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…We did not find a substantial direct effect of social origin on graduates' average occupational attainment throughout ten years after labour market entry. This finding is in line with previous results on UK graduates using the same dataset (e.g., most recently, Sullivan et al 2018aSullivan et al , 2018b. However, when we looked more closely at the effect of social origin on occupational prestige at different stages of the career, that is, extending previous snapshot analyses with a dynamic approach, our illustration of career patterns showed a slight disadvantage of working-class offspring compared to graduates from the higher social origin at labour market entry.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We did not find a substantial direct effect of social origin on graduates' average occupational attainment throughout ten years after labour market entry. This finding is in line with previous results on UK graduates using the same dataset (e.g., most recently, Sullivan et al 2018aSullivan et al , 2018b. However, when we looked more closely at the effect of social origin on occupational prestige at different stages of the career, that is, extending previous snapshot analyses with a dynamic approach, our illustration of career patterns showed a slight disadvantage of working-class offspring compared to graduates from the higher social origin at labour market entry.…”
Section: Discussionsupporting
confidence: 91%
“…The Blau-Duncan model already emphasized the importance of dynamic modelling and career progression for intergenerational mobility processes. However, many studies applied cross-sectional analyses to examine the direct effect of social origin on (graduates') labour market destination using population samples (e.g., Laurison and Friedman 2016;Wakeling and Savage 2015), considered outcomes at particular points in time during the career (Britton, Shephard, Vignoles and Dearden 2016;Crawford and Vignoles 2014;Macmillan, Tyler and Vignoles 2015) or at specific ages (Crawford et al 2016;Gugushvili, Bukodi and Goldthorpe 2017;Sullivan et al 2018aSullivan et al , 2018b. Jacob, Klein and Iannelli (2015) and Bukodi and Goldthorpe (2011) go beyond these single observations of labour market outcomes, but still, use only two-points-in-time measures of individual careers.…”
Section: Family Background and Graduate's Career Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…These divergent perceptions on the role of education highlight the need for more understanding. On one hand, education is seen as 'the great equaliser' (Torche 2011), explaining away the effect of social origin (Sullivan et al 2018) This optimistic view supports the notion that education bringing together students from wide socio-economic background, offering them more equal chances in the labour market upon graduation. Thus, educational attainment can compensate for the disadvantaged origin.…”
Section: Higher Educationmentioning
confidence: 74%
“…Some US studies found significant positive earnings effects (Brewer et al 1999;Hoekstra 2009;Loury and Garman 1995;Witteveen and Attewell 2017) or an advantage in occupational status (Brand and Halaby 2006) of the prestige of the institution attended, but other studies did not find effects on earnings (Dale and Krueger 2014; Dale and Krueger 2002;Long 2008). Similarly, for the UK, a few studies showed a wage premium of attending selective universities (Belfield et al 2018;Broecke 2012;Chevalier and Conlon 2003;Hussain et al 2009), but others were unable to detect differences in labor market outcomes (Sullivan et al 2018a;Walker and Zhu 2018).…”
Section: Introductionmentioning
confidence: 99%